Mutations and pemanences in ancient Palermo - Tiziana Firrone; Carmelo Bustino (Agathón)
Ancient Palermo identifies itself with its Historic Center whose complexity is the result of the encounter of successive cultures over the centuries and which gave the city its current facies. These sites are now a complex and articulated microcosm where the cultural models of the new inhabitants relate to the pre-existing, creating new forms and expressions of the anthropic intervention. The analysis is aimed at new urban scenarios, at footprints, at signs and at mutations created by a settlement process that involves new residents and their resources, in a field that has all the potential to return to Palermo its role as an international capital, with a view to integrating, welcoming, renewal and enhancing the enormous multicultural wealth accumulated in centuries of history.